O QUE HÁ DE NOVO NA REVISTA CONTEXTO & SAÚDE? - Heck, Thiago Gomes; Buratti, Giovano Pereira; Kolankiewicz, Adriane Cristina Bernat (Revista Contexto & Saúde, 2016)
O QUE HÁ DE NOVO NA REVISTA CONTEXTO & SAÚDE?